The Management of Crisis - EP CHEDLI, Mariem Kchaich (Journal of Economic Development, Environment and People, 2016)
Many business leaders defines a time of crisis as a moment which completely hinders society activity which ultimately leads to bankruptcy they prefer the choice of resentment downturn and do not consider it a key moment for the renewal ideas, ways of thinking, of policies and strategies adopted that mobilize around new ambitions, new development projects, new sales models, new businesses, new markets and do a crisis a moment of creation and innovation and collective revitalization. The purpose of this article is to study the various steps of the management of crisis and best management practices in times of crisis to be applied properly by the manager. Therefore, we would have to ask the following question: How can we ride a situation of crisis and provide benchmarks based on best management practices?